KONSTRUKSI PEMBERITAAN TERSANGKA RUSLI ZAINAL DI SURAT KABAR TRIBUN PEKANBARU - Wendi Kurniawan; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Governor Rusli Zainal known as prime mover for the region Riau South which include people who really cares and it was not easy to give up on the state. On the way his political career, in August 2012 Rusli stumble corruption cases PON XVII Riau. Then, in January 2013, Rusli examined in the bribery case, for eight hours. Until now this was the case was still in phase inspection. The determination of the suspect emerged Pros and cons Rusli zainal, research was meant to (1) knows the structure of the text particiberitaan suspects Rusli Zainal Newspapers Tribun (2) know Cognition Social Communication suspects Rusli Zainal in The Newspaper Tribun.This research uses qualitative analysis of the presentation descriptive. The analysis techniques that the used data is analysis of critical discourse that has been put forward by Teun A Van Dick. Data Collection will be done with technical documentation and an interview. But who is the subject this research is that the news that was found in The Newspaper Tribun Pekanbaru. While the one who became an object news coverage about the suspect Rusli Zainal in The Newspaper Tribun Pekanbaru since February 1 to March 30, 2013 and how reality.Result of this research first construction reality corruption suspects in coverage Rusli Zainal in the newspaper Tribun Pekanbaru based elements: theme, thus schematic, Semantics, Syntax, and Rhetorical. News In the contents are very few touched on how the role KPK in searching for evidence to determine the suspect was accused but many said that the role Rusli Zainal before a suspect. Both Cognition Social reality In the construction Corruption suspects In Coverage Rusli Zainal in the newspaper Tribun Pekanbaru in Cognition social journalists Tribun Pekanbaru as mental terekspresikan representation in the structure of the text that is displayed. More than that, the structure discourse language is also the attitudes, beliefs, views, norms, values, the rules, and the knowledge that is owned by journalists Tribun Pekanbaru and in the newspaper readers cognition Tribun Pekanbaru, that the newspaper Tribun provides information that was equal to that other newspapers and their own language teaching.Keywords: Construction; Coverage suspect Rusli Zainal; Tribune Newspaper